Personal values, trait emotional intelligence, and mental health problems. Issue 2 (3rd November 2021) - Jacobs, Ingo; Wollny, Anna
Abstract : Personal values and personality traits are related yet distinguishable constructs linked to mental health. The present study extends the current literature on personal values and personality traits by investigating the associations between the higher‐order dimensions of personal values (i.e., general values factor, conservation, and self‐transcendence), trait emotional intelligence (TEI), and mental health problems (i.e., depressive, anxiety, and somatoform syndromes). The study draws on a cross‐sectional online sample of N = 618 young German adults. Global TEI and all four TEI factors (i.e., well‐being, sociability, emotionality, and self‐control) correlated positively with the g‐value factor but negatively with conservation. Emotionality was also positively related to self‐transcendence. Mental health problems correlated positively with conservation and negatively with the general values factor. When the effects of global TEI were accounted for, conservation but not the general values factor remained significantly related to mental health problems. Global TEI fully mediated the relationship between the g‐value factor and mental health problems and partially mediated the association between conservation and mental health problems. The implications of these results are discussed.